Psychological and Demographic Predictors of Vaping and Vaping Susceptibility in Young Adults - Teah, Grace E.; Conner, Tamlin S. (Frontiers in Psychology, 2021)
Background The use of electronic nicotine delivery systems (ENDS), also known as vaping, is becoming popular among young adults. Few studies have explored the psychological factors that predict ENDS use and susceptibility in young adults, in addition to known demographic predictors. Method In a cross-sectional survey design, 521 young adults (37% male), ages 18–25 from the United States, were recruited via Amazon’s Mechanical Turk (MTurk) in 2019, to answer an online survey measuring demographic characteristics and psychological characteristics related to mental health and the Big Five personality traits. The survey also included measures of ENDS ever-use, current use, and susceptibility (never users open to trying ENDS), which we predicted from the demographic and psychological measures using independent and multiple binary logistic regression analyses. Results Of those surveyed (n = 521), 282 (54.1%) were ENDS ever-users, 93 (17.9%) were current ENDS users, and 61 (11.7%) were ENDS susceptible; 62 (11.9%) were current smokers. Demographically, young adults lower in adulthood socioeconomic-status (SES), not pursuing education further than high school, and current smokers were more likely to be ENDS users. Psychologically, young adults higher in anxiety and lower in conscientiousness more likely to have ever-used ENDS. Lower conscientiousness further predicted current ENDS use and ENDS susceptibility. Conclusion In this sample of MTurk workers, young adults with experience in vaping were more demographically and psychologically vulnerable than young adults with no experience in vaping. Young adults interested in vaping, but without prior experience, were less conscientious than their non-interested peers. Interventions to target vaping use should focus on economically disadvantaged young adults and those lower in conscientiousness.